2019
DOI: 10.12944/crnfsj.7.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extracts of Ficus carica Fruit and Leaf Normalize High Serum Lipid Profile, TNF-α, and MDA due to High Fat Diet in Sprague Dawley Rat

Abstract: Dyslipidemia is one of the main risk factors for cardiovascular disease (CVD). Ficus carica fruit and leaf contain polyphenolic compounds that can inhibit lipid peroxidation. Our research aimed to study the effect of ethanol extract of F. carica fruit (FcFrEx) and F. carica leaves ( FcLfEx ) on serum lipid (total cholesterol, LDLchol, HDLchol, Triglyceride (TG)), TNF-α, and MDA levels in rat fed a high-fat diet. This experiment was a randomized control group design with pre and post-test using 32 male Sprague … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has been shown that the supplementation of a high-fat diet with F. sycomorus leaves depressed serum high density lipoprotein (HDL), L-histidinol LHL, cholesterol, and triglycerides in rats [44]. Furthermore, a significant reduction in the HDL, LDL, total cholesterol, and triglycerides was detected in Sprague Dawley rats fed with a high-fat diet along with either Ficus carica fruit or leaf ethanolic extract at a dose of 400 mg/kg BW [49]. These extracts could ameliorate dyslipidemia due to supplementation with a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the supplementation of a high-fat diet with F. sycomorus leaves depressed serum high density lipoprotein (HDL), L-histidinol LHL, cholesterol, and triglycerides in rats [44]. Furthermore, a significant reduction in the HDL, LDL, total cholesterol, and triglycerides was detected in Sprague Dawley rats fed with a high-fat diet along with either Ficus carica fruit or leaf ethanolic extract at a dose of 400 mg/kg BW [49]. These extracts could ameliorate dyslipidemia due to supplementation with a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Triglycerides were determined using the GPO-PAP method (DiaSys) 13 Total Cholesterol (TC) Assay Whole blood was obtained after 12 hours of fasting from the venous plexus retro orbitalis of rats and then centrifugated to separate the serum. TC was determined by the CHOD-PAP method (DiaSys) 13 High Density Lipoprotein Cholesterol (HDL-C) Assay Serum (0.02 mL) was added to 0.5 mL of sediment solution, then the mixture was centrifuged for about 20 minutes at 4500 rpm. The supernatant (0.01 ml) was mixed with 1 mL cholesterol reagent.…”
Section: Triglyceride (Tg) Assaymentioning
confidence: 99%
“…HDL cholesterol was assayed using the CHOD-PAP (DiaSys) method by the same procedure as for TC. 13 Low Density Lipoprotein Cholesterol (LDL-C) Assay LDL was determined directly using the CHOD-PAP method and precipitant LDL. Serum of 100 µL was mixed with 1000 µL precipitating reagent and incubated for 15 minat room temperature, then centrifuged for 20 min at 2500 g. Within one hour after centrifugation, 100 µL of the clear supernatant was transferred to the reaction solution for determination of cholesterol.…”
Section: Triglyceride (Tg) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetables are well-known key components of the human diet and are beneficial because of the presence of diverse phytonutrients, such as polyphenols, flavonoids, and carotenoids, which have strong antioxidant properties [1][2][3]. These ameliorate, prevent, or reverse several undesirable effects of metabolic syndromes, such as dyslipidaemia, oxidative stress status, hyperglycaemia, and obesity [4][5][6][7]. Green leafy vegetables, the flowery part of vegetables, and/or the sprouts of some beans have been part of the daily diet in Southeast Asian countries.…”
Section: Introductionmentioning
confidence: 99%